2022
DOI: 10.3390/ijerph19116859
|View full text |Cite
|
Sign up to set email alerts
|

24 Hours on the Run—Does Boredom Matter for Ultra-Endurance Athletes’ Crises?

Abstract: Sport and exercise can be boring. In the general population, thinking of sports as boring has been linked to exercising less. However, less is known about the role of boredom in people who participate in ultra-endurance competitions: Do these athletes also associate their sports with boredom, and does boredom pose a self-regulatory challenge that predicts if they encounter a crisis during an ultra-endurance competition? Here, we investigate these questions with a sample of N = 113 (n = 34 female) competitors o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…In one study, extreme sport athletes (snowboarders, climbers) displayed lower boredom proneness than e-sport athletes 85 . In the second study, ultra-endurance runners scored lower on a measure of sport-specific trait boredom than less extreme runners 83 . These studies indicate that athletes' boredom proneness differs across sports and across athletic levels.…”
Section: When It's Not Only About Participation: Boredom In Performan...mentioning
confidence: 88%
See 1 more Smart Citation
“…In one study, extreme sport athletes (snowboarders, climbers) displayed lower boredom proneness than e-sport athletes 85 . In the second study, ultra-endurance runners scored lower on a measure of sport-specific trait boredom than less extreme runners 83 . These studies indicate that athletes' boredom proneness differs across sports and across athletic levels.…”
Section: When It's Not Only About Participation: Boredom In Performan...mentioning
confidence: 88%
“…Beyond training, one study investigated the prevalence and relevance of experiencing boredom during ultra-endurance competitions. Interestingly, boredom was reported less frequently than more prototypical exercise-induced sensations such as fatigue or pain; but only boredom emerged as a statistically significant correlate of having had a crisis during competition 83 . This highlights that a sensation does not need to be experienced very intensely or frequently to alter performance.…”
Section: When It's Not Only About Participation: Boredom In Performan...mentioning
confidence: 92%
“…While boredom is prototypically understood as something that occurs in situations that are underchallenging and of low arousal (van Tilburg & Igou, 2017; Vogel-Walcutt et al, 2012; see also Bieleke et al, 2021; Westgate & Wilson, 2018), a recent study showed that boredom can even occur during very hard efforts that are performed until exhaustion (Hirsch et al, 2021). In another vein, a study that was conducted with ultraendurance runners competing in a 24-hr running competition showed that trait measures of boredom predicted how much the athletes struggled with boredom during their competition and that the experience of boredom during the competition was a predictor of whether an athlete had experienced a crisis during their run (Weich et al, 2022). Taken together, these types of studies show that boredom seems to accompany training in various sporting contexts (i.e., training and competitions), and the presence of boredom might impair sporting performance.…”
Section: Theoretical Foundations Of Boredommentioning
confidence: 99%
“…While boredom is prototypically understood as something that occurs in situations that are under-challenging and of low arousal (Van Tilburg & Igou, 2017;Vogel-Walcutt et al, 2012; see also Westgate & Wilson, 2018), a recent study showed that boredom can even occur during very hard efforts that are performed until exhaustion (Hirsch et al, 2021). In another vein, a study that was conducted with ultra-endurance runners competing in a 24-hour running competition showed that trait measures of boredom predicted how much the athletes struggled with boredom during their competition, and that the experience of boredom during the competition was a predictor of whether an athlete had experienced a crisis during their run (Weich et al, 2022). Taken together, these types of studies show that boredom seems to accompany training in various sporting contexts (i.e., training and competitions), and the presence of boredom might impair sporting performance.…”
Section: Boredom In Sportsmentioning
confidence: 99%
“…Interestingly, while recent work has shown that boredom matters during competitions (Weich et al, 2022), relatively little is known about the effects of boredom during training.…”
Section: Boredom In Sportsmentioning
confidence: 99%